Emissão de óxido nitroso e mineralização do carbono de plantas de cobertura e de dejetos suínos e bovínos em plantio direto de mamona - Santos, Gabriel de Franceschi dos (2009)
The increase in the availability of nutrients to soil microorganisms, especially carbon (C) and nitrogen (N), through crop residues and animal slurries can increase dioxide carbon (CO2) and nitrous oxide (N2O) emissions to the atmosphere. In order, to evaluate this hypothesis, two studies in field conditions were conducted in a typic Hapludalf at experimental area of Soils Department of UFSM-RS. The evaluated treatments were: T1-crop residues (CR) of oat; T2-CR of oat + pig slurry (PS); T3-CR oat + dairy cattle slurry (DCS); T4- CR of oat + N (urea); T5-CR common vetch, T6- CR of mixture between oat+vetch; and T7-fallow. The assessments started soon after the management of cover crops and application of animal slurries. The first study, evaluated the CO2 emission continuously for a period of 99 days. In the second study, it was evaluated the N2O emissions during 322 days. The inclusion of oat in mixture with vetch reduced the C mineralization rate of the CR, which was inversely proportional to the C/N ratio of CR, and followed this order: vetch> oat+vetch> oat. The addition of mineral N with DCS, did not increase the C mineralization of oat straw. The DCS application on the oat straw decreased C mineralization of slurry in relation to their application on the bare soil. The largest N2O fluxes occurred in the first days after the management of cover crops and application of animal slurries. The DCS were organic residue wich promoted greatest cumulative N2O emissions. In favorable conditions for the N2O emission in the soil, the production of this gas seems to be dependent on the C availability in soluble form.